Pemenuhan Kebutuhan Dasar Psikologis dan Engagement Siswa Pada Pelajaran Matematika - Putri Sukma Deri; Surya Cahyadi; Erna Susiati (Jurnal Ilmu Perilaku, 2019)
Abstract. Engagement in learning activities is important to get the knowledge and skills provided at school. Previous studies on engagement prove that engagement is a predictor of student learning, learning outcomes, student retention and graduation. Therefore, to be able to make students more engaged with learning activities, it is necessary to know the factors that can influence the engagement. In this study, we will examine the effect of fulfilling need for autonomy, competence and relatedness on behavioral and emotional engagement. Measurements were made by distributing questionnaires in the form of self-reports to respondents. Respondents from this study were 291 students of class VII and VIII MTs Jatinangor. The data analysis technique used is PLS-SEM, path analysis. The results showed that behavioral and emotional engagement were positively and significantly influenced by meeting the needs of competence and relatedness. Then it was also found that this engagement was influenced negatively and significantly by autonomy needs.